DINAMIKA POLA PERILAKU KERJA DALAM BUDAYA ORGANISASI BIROKRASI: STUDI KASUS DI KANTOR KECAMATAN BIRINGKANAYA - Haerul, Haerul; Nasir (STISIP Widyapuri Mandiri Sukabumi, 2025)
Organizational culture has an important role in shaping employee work behavior, especially in the public sector bureaucratic environment. This research is motivated by the need for an in-depth understanding of how the values, norms, and habits that develop in sub-district government organizations affect the productivity and effectiveness of employee work. The purpose of this study is to describe and analyze the dynamics of work behavior patterns in the context of organizational culture in the Biringkanaya District Office, Makassar City. This study uses a qualitative approach with a descriptive study type. Data was collected through in-depth interviews, direct observations, and documentation, with key informants consisting of structural officials, service staff, and community leaders. Data analysis was carried out interactively with the Miles, Huberman, and Saldana models, through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the organizational culture at the Biringkanaya District Office is dominated by the values of loyalty, obedience, and solidarity between employees. Work behavior patterns tend to be hierarchical, but also contain informal practices such as mutual cooperation. Leadership factors, internal communication, and institutional loyalty are the cultural elements that most influence work productivity. The recommendations of this study are the importance of building a more participatory, adaptive, and performance-based organizational culture, in order to increase bureaucratic responsiveness to the dynamics of urban society.